The factors that affect customer satisfaction on the quality of hotel service - Siti Maryam Hanah Abdul Kadir; Siti Najihah Shamsuddin; Siti Najwa Ashikin Mohd Shamsudin; Siti Nazifah Anisa Md Nasir (2023)
The purpose of this study is to look into the relationship between service quality and customer satisfaction in Malacca hotels by using SERVQUAL analysis. It also aims to investigate the influence and effect of providing quality service on customer satisfaction, as well as to determine which SERVQUAL dimension has the greatest influence on customer satisfaction. The SERVQUAL dimensions of tangibility, assurance, and reliability have been identified as independent variables, while customer satisfaction has been identified as a dependent variable. Each dimension was tested in order to determine and quantify the relationship with customer satisfaction. Customers who had stayed in Malacca hotels completed the questionnaires. A total of several respondents participated in the survey. The findings of the research show that the service quality provided by the hotels can affect customer’s satisfaction.